Our system is currently under heavy load due to increased usage. We're actively working on upgrades to improve performance. Thank you for your patience.
2016
DOI: 10.18052/www.scipress.com/ijppe.5.60
|View full text |Cite
|
Sign up to set email alerts
|

Effects of Oral Administration of D-002 (Beeswax Alcohols) on Histological and Functional Outcomes in a Rat Model of Antigen-Induced Arthritis: Preliminary Study

Abstract: Abstract. D-002, a mixture of higher aliphatic beeswax alcohols, has been shown to display antiinflammatory effects associated with the dual inhibition of ciclooxygenase and 5-lipoxygenase. Oral D-002 supplementation has been effective in experimental osteoarthritis, ameliorating all features of joint histopathology. Clinical studies have demonstrated that D-002 reduces osteoarthritis symptoms. However, D-002 effects on experimental models of rheumatoid arthritis (RA) have not been evaluated. To investigate wh… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
2
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
2
1

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(5 citation statements)
references
References 27 publications
0
2
0
Order By: Relevance
“…Despite the many papers from animal and human studies showing that supplementation of BWA ameliorated gastric ulcers, esophagitis, and osteoarthritis [10,11,56], the in vitro antioxidant abilities of BWA and the mechanism of antioxidant activity after oral ingestion were not fully elucidated. Although BWA has adequate DPPH radical scavenging activity and ferric ion reduction ability in ethanol solvent assay systems [57], the current results showed that the incorporation of BWA in rHDL resulted in more enhancement of HDL-associated PON and FRA activity to inhibit LDL oxidation.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Despite the many papers from animal and human studies showing that supplementation of BWA ameliorated gastric ulcers, esophagitis, and osteoarthritis [10,11,56], the in vitro antioxidant abilities of BWA and the mechanism of antioxidant activity after oral ingestion were not fully elucidated. Although BWA has adequate DPPH radical scavenging activity and ferric ion reduction ability in ethanol solvent assay systems [57], the current results showed that the incorporation of BWA in rHDL resulted in more enhancement of HDL-associated PON and FRA activity to inhibit LDL oxidation.…”
Section: Discussionmentioning
confidence: 99%
“…Beeswax alcohol (BWA), a beeswax-extracted substance, comprises a blend of six main aliphatic alcohols (of carbon chains 24, 26, 28, 30, 32, and 34) that demonstrate antioxidant, anti-platelet, cholesterol-lowering, and gastroprotective properties [8,9]. Notably, supplementing with BWA enhanced the production and quantity of gastric mucus in rat models with ethanol-induced ulcers and mitigated inflammation in cases of antigen-induced arthritis [10,11]. BWA is acknowledged for safeguarding the body against oxidative stress, promoting a healthy stomach by protecting the gastric mucosa, and contributing to maintaining joint health.…”
Section: Introductionmentioning
confidence: 99%
“…Despite the many papers from animal and human studies showing that supplementation of BWA ameliorated gastric ulcers, esophagitis, and osteoarthritis [10,11,50], the in vitro antioxidant abilities of BWA and the mechanism of antioxidant activity after oral ingestion were not fully elucidated. Although BWA has adequate DPPH radical scavenging activity and ferric ion reduction ability in ethanol solvent assay systems [52], the current results showed that the incorporation of BWA in rHDL resulted in more enhancement of HDL-associated PON and FRA activity to inhibit LDL oxidation.…”
Section: Discussionmentioning
confidence: 99%
“…Beeswax alcohol (BWA), a substance purified from beeswax, contains a mixture of six primary aliphatic alcohols (C24, C26, C28, C30, C32, and C34) with antioxidant, anti-platelet, cholesterollowering, and gastroprotective effects [8,9]. In particular, BWA supplementation promoted the secretion and quality of gastric mucus in ethanol-ulcer rat models and attenuated inflammation in antigen-induced arthritis [10,11]. With these properties, BWA has been registered as a functional food ingredient to help protect the body from oxidative stress, maintain a healthy stomach by protecting the gastric mucosa, and maintain joint health in Korean health functional foods according to the Ministry of Food and Drug Safety (MFDS, https://www.foodsafetykorea.go.kr/portal/board/board Detail.do?menu_grp=MENU_NEW01&menu_no=2660&bbs_no=bbs987&nticmatr_yn=N&bbs_type _cd=01&ans_yn=N&ntctxt_no=21590).…”
Section: Introductionmentioning
confidence: 99%
“…However, the most noteworthy role of BWA was established as a gastroprotective agent. Several pharmacological and clinical studies confirmed the impact of BWA on the quantity and quality of gastric mucous [14,15]. Recently, the Korean Food and Drug Administration (KFDA) approved BWA as a functional food ingredient for improving joint and gastrointestinal health [12].…”
Section: Introductionmentioning
confidence: 97%